2021
DOI: 10.1002/smll.202105147
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Lysozyme from Chicken Albumen Using Polyelectrolyte Complexes

Abstract: Cells use droplet‐like membrane‐less organelles (MLOs) to compartmentalize and selectively take‐up molecules, such as proteins, from their internal environment. These membraneless organelles can be mimicked by polyelectrolyte complexes (PECs) consisting of oppositely charged polyelectrolytes. Previous research has demonstrated that protein uptake strongly depends on the PEC composition. This suggests that PECs can be used to selectively extract proteins from a multi‐protein mixture. With this in mind, the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Protein-PE complexes are being implemented in various industrial and biotechnological applications ranging from protein purification [ 3 , 4 , 5 , 6 ], enzyme activation [ 7 ], drug delivery [ 8 , 9 , 10 ], biosensors [ 11 ], stabilization in food emulsions [ 12 ] etc. Protein-PE interactions are also important in in vivo processes such as the formation of membraneless organelles [ 5 , 13 ] through liquid-liquid phase separation or the interaction between natural polyelectrolytes (DNA) and proteins (histones) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein-PE complexes are being implemented in various industrial and biotechnological applications ranging from protein purification [ 3 , 4 , 5 , 6 ], enzyme activation [ 7 ], drug delivery [ 8 , 9 , 10 ], biosensors [ 11 ], stabilization in food emulsions [ 12 ] etc. Protein-PE interactions are also important in in vivo processes such as the formation of membraneless organelles [ 5 , 13 ] through liquid-liquid phase separation or the interaction between natural polyelectrolytes (DNA) and proteins (histones) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many theories and experiments investigated the partitioning of monovalent salts, much less is known about the partitioning of multivalent ions , or small organic molecules. , In brief, these experimental studies have shown that multivalent ions generally tend to accumulate in the PEC phase. Furthermore, the partitioning of multivalent solutes depends also on their size, hydrophobicity, and charge.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] One of its main features is in the purification of proteins given that it is a relatively low-cost technique. [6][7][8] Whey proteins are found in cheese whey, which is a byproduct of the dairy industry. Currently, cheese whey serves as a cost-effective protein source with numerous applications in the food industry.…”
Section: Introductionmentioning
confidence: 99%